Biologia e ecologia de ermitões (Crustacea, Anomura) do sublitoral não consolidado do sudeste brasileiro - Lima, Israel Fernandes Frameschi de [UNESP] (2014)
Dardanus insignis is the most abundant hermit crab on sublittoral of soft bottoms along the southeastern coast of Brazil. It is among the Decapoda species that structure the macrobenthic community, from shallow regions to deeper areas up to 100 m. This study evaluated the distribution of D. insignis in a tropical-subtropical transition zone. In three bays (Ubatumirim, Ubatuba and Mar Virado), sampling was conducted monthly for two years, on four transects parallel to the coastline (at depths of 5, 10, 15, and 20 m), as well as one transect sheltered from wave action, and another in a more exposed area. Environmental variables were monitored in each sampling. The study sites differed in water temperature, salinity, organic-matter content and substrate composition. The size fractions of coarse, medium and fine sand were correlated mainly with Ubatumirim and Ubatuba bays, on transects 15 and 20 m deep. The distribution of demographic groups showed a positive relationship with these variables, with large numbers of individuals found in Ubatuba and on the deepest transects. These results suggest that living farther from the coast might provide protection for D. insignis against the oscillation of environmental variables, especially those that are affected by rainfall regimes, such as the sediment